Match demands of senior and junior players during International Rugby League - Dempsey, G. M.; Gibson, N. V.; Sykes, D.; Pryjmachuk, B. C.; Turner, A. P. (The Journal of Strength and Conditioning Research, 2018)
This study aims to quantify and compare the positional game demands of international junior and senior rugby league competition for the first time. Global positioning system (GPS) and video analysis were used to track 118 elite male rugby league players (57 seniors aged 28.7 ± 4.4 years; 61 juniors aged 17.2 ± 0.5 years) over 10 international matches (6 senior; 4 junior) characterized as either forwards (n = 67) or backs (n = 51). There were significant increases in the offensive carries (0.18 cf. 0.09 n/min; r = 0.56) and defensive tackles (0.36 cf. 0.23 n/min; r = 0.3) between senior and junior players, and forwards and backs (0.16 cf. 0.09; r = 0.34 and 0.41 cf. 0.14; r = 0.52), respectively. Running demands were significantly greater in backs than forwards (independent of playing level) for total distance (6,962 ± 1,263 m cf. 4,879 ± 1,824 m; r = 0.55), individualized high-speed distances (310 ± 158 m cf. 250 ± 171 m; r = 0.2), high-intensity accelerations (28.7 ± 12.1 m/s cf. 21.9 ± 11.7 m/s; r = 0.27), and decelerations (57.2 ± 18.3 m/s cf. 43.0 ± 17.8 m/s; r = 0.38). Positional differences were eliminated when reported relative to minutes played. From a practical perspective, although running demands relative to time on the pitch may prepare junior players for senior competition, it is not representative of the increased body mass and contact frequency within the senior game. Coaches should therefore reflect these differences within their physical preparation programs to prepare junior athletes accordingly for progression to the senior level.